Factors affecting stillbirth: prospective study - Jadhav, Balaji; Khade, Shweta Avinash; Shinde, Ganesh; Chandan, Shilpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Stillbirth is defined by WHO as the birth of a baby with a birth weight of 500 gm or more, 22 or more completed weeks of gestation or a body length of 25 cm or more, who died before or during labour and birth. Methods: This was prospective observational study of factors affecting stillbirth was conducted in tertiary hospital for a period of 1 year from 1st June 2014 to 31st May 2015. During the study period, 200 parturient of gestational age 28 weeks or more and fetal weight 1000 gm or more with or without medical disorders were included. Results: The total number of births during study period was 11,951. Stillbirth rate in the present study was 16.73 per 1000 births. Most of stillbirths were seen in the antepartum period (76%) when compared to intrapartum period (24%). Maximum stillbirths occurred in gestational age of 36 weeks and above (52%) and fetal weight between 2001-2500 gm (27.50%). Patients with inadequate antenatal care, less than three visits had 86% stillbirths. Conclusions: Proper antenatal care, prompt referral services and availability of emergency obstetric care will provide a pivotal role for reduction of stillbirths.